2013 IEEE China Summit and International Conference on Signal and Information Processing 2013
DOI: 10.1109/chinasip.2013.6625404
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of energy detection for spectrum sensing in cognitive radio over Nakagami-lognormal composite channels

Abstract: This paper is concerned with the performance of energy detection for spectrum sensing in cognitive radio. Both fading and shadowing are considered by assuming a Nakagamilognormal composite channel model. Based on a newly-derived exponential integral representation for the generalized Marcum Q-function, performance analysis of energy detection is formulated as a unified moment generating function (MGF) approach. Energy detection without diversity is addressed first. The proposed MGF approach is then extended to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It is worth noting that a direct analysis of the ED performance in composite fading channels is rather tedious, since composite fading models can only be represented by infinite integrals. The probability of detection of the ED is derived over Nakagami-lognormal (NL) fading channels in [13]. However, the offered solution is not represented in closed form and the impact of fading and shadowing effects is investigated numerically.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that a direct analysis of the ED performance in composite fading channels is rather tedious, since composite fading models can only be represented by infinite integrals. The probability of detection of the ED is derived over Nakagami-lognormal (NL) fading channels in [13]. However, the offered solution is not represented in closed form and the impact of fading and shadowing effects is investigated numerically.…”
Section: Introductionmentioning
confidence: 99%
“…In [37], i.i.d. L Nakagami-m lognormal composite 1 channel branches was investigated without and with SLC and SLS diversity, and MGF based approach was derived.…”
Section: Related Workmentioning
confidence: 99%
“…In this context, the ED performance over multipath fading channels, such as Rayleigh, Rician, and Nakagamim was analyzed in [14], and [15], respectively, whereas the corresponding performance over the more generalized κ − µ and κ − µ extreme fading channels was investigated in [16]. However, in addition to multipath fading, in most scenarios, the received signal is also degraded by shadowing effects since it has been shown that multipath and shadowing effects typically occur simultaneously [17]. Therefore, it is evident that there is an undoubted necessity to quantify and analyze the CR performance over composite multipath/shadowing fading channels [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been shown that such an analysis is particularly tedious, since composite fading models can only be represented by cumbersome, if not intractable, infinite integrals. For example, the probability of detection of the ED based spectrum sensing over Nakagami-lognormal (NL) fading channels was addressed in [17]; yet, the offered solution is semi-analytic, as it is not represented in closed form, while the impact of fading and shadowing effects is evaluated numerically. Based on this, several alternative models that characterize the composite fading channels have been shown to provide simplified performance analysis for the CR networks.…”
Section: Introductionmentioning
confidence: 99%